Fatty acid methyl ester analysis of Aspergillus fumigatus isolated from fruit pulps for biodiesel production using GC-MS spectrometry - Asci, FerruhS; Aydin, Busra; Akkus, Gulderen Uysal; Unal, Arzu; Erdogmus, Sevim Feyza; Korcan, Safiye Elif; Jahan, Israt (TAYLOR & FRANCIS INC, 2020)
In this study, a total of six fungal samples were isolated from apple, strawberry and orange pulp. DNA sequence analysis was used as molecular identification method. ITS region was aligned in DNA sequence analysis, and an algorithm sequence similarity was done using BLAST (Basic Local Alignment Search Tool) program to identify these isolates. All the six isolates were identified as Aspergillus fumigates. The total lipid content was varied in the isolates which were ranged from 29.4 to 21.0 mg/100 ml. Moreover, the obtained lipid form mycelium biomass of the isolates was transesterified by a base catalyst. The methyl esters were analyzed by using GC-MS. GC-MS Spectrometry revealed the presence of different fatty acids with long chain (C11:0, C15:0, C17:1, C18:2, C16:1). High efficiency biodiesel can be obtained using long-chain fatty acids. Fatty acid profiles of A. fumigatus isolated from different fruit pulps have confirmed its potentiality as well as showed the beneficial utilization of these fatty acids for biodiesel production.
Keywords: Aspergillus fumigates; fatty Acid Methyl Ester; biodiesel; fungal lipids; GC-MS analysis; FILAMENTOUS FUNGI; LIPIDS; Biotechnology & Applied Microbiology